Widespread Perversion: Alain Robbe-Grillet Reconsidered from the Point of View of Evil - Grossi, Bruno (2022)
This article analyzes the two readings that historically guided the reception of Le Voyeur (1955) by Alain Robbe-Grillet: A formalist reading attentive to the multiplicity of writing procedures but, for that reason, she made abstracts out of the themes contained in the text and another that focuses the thematic study by analyzing the diegetic material of the text with a psychopathologizing look. However, the novel, far from moralizing its erotic-violent content, stages the different ways in which culture represents sexual fantasies that, although they constitute it, it cannot bear except in displaced forms. Our hypothesis holds that Robbe-Grillet immerses himself into such evil images, but rather than distancing himself from or rejecting them, he tends to fortify and intensify them through his own objectivist and impersonal technique. The result of such procedures allows us to finally rethink the ambiguous relations between aesthetics and morals that follow from the poet's poetics.